Celiac Disease in Bangladesh Two Case Reports (Bangladesh Journal of Child Health, 2013)
Celiae disease is an immunological disorder precipitated by gluten in genetically susceptible persons. Its prevalence is not known in Bangladesh because of unavailability of its screening test. There is diversity in the presentation of celiac disease. Two children of 5 and 8 years of age who were diagnosed as celiac disease are reported here. One presented typically with chronic diarrhoea & growth failure. Another child presented with features of chronic liver disease. In both the cases IgA tTGA were positive and duodenal biopsy showed villous atrophy. After diagnosis, both the patients were kept on gluten free diet (GFD). After six months of GFD, IgA tTGA came down to normal in both the cases. They were then given gluten containing diet again & after few months IgA tTGA again raised in both the cases. Thereafter the cases were finally diagnosed as celiac disease and were advised life long gluten free diet. Celiac disease is not uncommon in Bangladesh and screening test should be done to diagnose or rule out celiac disease when there is a suspicion. DOI: http://dx.doi.org/10.3329/bjch.v37i1.15351 BANGLADESH J CHILD HEALTH 2013; VOL 37 (1) : 45-48